Increased Circulating Th1 and Tfh1 Cell Numbers Are Associated with Disease Activity in Glucocorticoid-Treated Patients with IgG4-Related Disease. (30th November 2020) - Xia, Changsheng; Liu, Caoyi; Liu, Yanying; Long, Yan; Xu, Lijuan; Liu, Chen
Abstract : Background . This study is aimed at exploring the changes and significance of circulating Th and Tfh cell subsets in glucocorticoid-treated IgG4-RD patients. Methods . 39 glucocorticoid-treated IgG4-RD patients and 22 healthy controls (HC) were enrolled. Peripheral blood mononuclear cells were separated, and circulating Th and Tfh cell subsets were examined by flow cytometry according to the surface and intranuclear markers. Disease activity was accessed by the IgG4-RD responder index (RI) score. Correlation analyses were conducted between Th/Tfh subset numbers and clinical indicators. The receiver operating characteristic (ROC) curve was used to evaluate the efficacy of Th and Tfh subsets to distinguish active IgG4-RD patients from remission IgG4-RD patients. Results . Circulating Th1, Th17, Tfh1, and Tfh17 cells were significantly increased in active IgG4-RD patients compared with HC. Th1 and Tfh1 numbers were positively correlated with serum IgG4 levels in patients with IgG4-RD. Meanwhile, the absolute numbers of circulating Th1 and Tfh1 cells were positively correlated with IgG4-RD RI scores. The areas under the curve (AUC) were 0.8276 for Th1 and 0.7310 for Tfh1, 0.5862 for Tfh2, and 0.6810 for Tfh17. Conclusion . Increased circulating Th1 and Tfh1 subsets are related to elevated serum IgG4 levels in active IgG4-RD patients during glucocorticoid treatment, which may play an important role in the course of IgG4-RD disease, and could be potential biomarkers for monitoring disease activity of IgG4-RD.